Ransom Canyon - Thomas, Jodi (Thomas, Jodi. Ransom Canyon romance, 2015)
"Rancher Staten Kirkland, the last descendant of Ransom Canyon's founding father, is rugged and practical to the last. No one knows that when his troubling memories threaten to overwhelm him, he runs to lovely, reclusive Quinn O'Grady, or that she has her own secret that no one living knows. Young Lucas Reyes has his eye on the prize--college, and the chance to become something more than a ranch hand's son. But one night, one wrong decision, will set his life on a course even he hadn't imagined. Yancy Grey is running hard from his troubled past. He doesn't plan to stick around Ransom Canyon, just long enough to learn the town's weaknesses and how to use them for personal gain. Only Yancy, a common criminal since he was old enough to reach a car's pedals, isn't prepared for what he encounters" --